High Gain of Cascode LNA at 5.8GHz Using T-Matching Network for wireless Applications - Ibrahim , A.B; Othman , A.R; Husain, M.N; Johal , M.S (2011)
This paper presents a design of high gain single stage cascode low noise amplifier (LNA), which operates at 5.8GHz frequency for WIMAX application. The LNA design used T-Matching network consisting of lump reactive element at input and output matching. The design simulation process is using Advance Design System (ADS) software. A cascode low noise amplifier (LNA) produced gain of 19.52dB and noise figure (NF) at 1.195dB. The input reflection (S11) and output return loss (S22) are -18.86dB and -19.49dB respectively. The bandwidth of the amplifier is more than 1GHz. The input sensitivity is complying with the IEEE 802.16 standards. The LNA used FHX76LP low noise SuperHEMT FET transistor from Eudyna Inc.